Meningococcal Antibiotic Resistance: Molecular Characterization of Isolates from Patients with Invasive Meningococcal Disease (IMD) in Greece - Ioanna Spiliopoulou; Athanasia Xirogianni; Stelmos Simantirakis; Georgina Tzanakaki (MDPI AG, 2023)
For effective case management and chemoprophylaxis of Invasive Meningococcal Disease (IMD), prompt antibiotic treatment is required. N. meningitidis is usually susceptible to antibiotics, but reduced susceptibility to penicillin, ciprofloxacin, and rifampicin is increasing worldwide, jeopardizing patients' outcome. We assessed, phenotypically and genotypically, the antimicrobial resistance patterns of 192 strains isolated from IMD cases from all over Greece during 2010-2021. Antimicrobial susceptibility to penicillin, rifampicin, and ciprofloxacin was determined using the E-test. All isolates were genotyped by Multilocus Sequence Typing (MLST). penA, rpoB, and gyrA genes were amplified by PCR and sequenced. Of the 192 isolates, 37% (72/192) were penicillin-susceptible/had increased exposure, and 11% (21/192) were penicillin-resistant. Among those, 40 penA alleles were identified; penA1, penA27, and penA3 were highly associated with susceptibility to penicillin; penA14, penA25, and penA22 related to reduced susceptibility to penicillin, while penA9, penA910, and penA295 had resistance to penicillin. Two ciprofloxacin-resistant isolates harbored the gyrA346 allele, while one rifampicin-resistant isolate harbored the rpoB5 allele. Resistance to ciprofloxacin and rifampicin remains rare. As Greece is one of the countries with high antimicrobial resistance, continued monitoring of antibiotic resistance is important to ensure timely detection of emerging resistance for treatment and prevention guidelines.